Geospatial cost and emission assessment of universal fiber-to-the-neighborhood (FTTnb) broadband infrastructure strategies for Sub-Saharan Africa - Ogutu B Osoro; Edward J Oughton; Fabion Kauker (Environmental Research: Infrastructure and Sustainability)
Currently, fixed fiber infrastructure is essential for providing universal broadband but has received relatively little research attention in low-income countries compared to other more cost-efficient wireless technologies. Yet, pushing out fiber broadband to local areas is essential, even if the final access network is still wireless. Here, we design least-cost fiber-to-the-neighborhood (FTTnb) architectures using two spatial optimization Steiner tree algorithms to jointly determine investment costs, environmental emissions, and social carbon costs. We find that the average annualized per user emissions in low population density areas (<9 people per km ^2 ) range from 1.9 ± 0.05 kg CO _2 e to 9.6 ± 0.24 kg CO _2 e, compared to 0.02 ± 0.001 kg CO _2 e to 0.12 ± 0.004 kg CO _2 e for high population density areas (>958 people per km ^2 ). Moreover, total cost of ownership for building fiber closer to premises is approximately US$ 2.1 ± 0.16 billion in high population density areas (>958 people per km ^2 ) compared to US$ 64 ± 3.5 billion for sparsely populated regions (<21 people per km ^2 ). The findings suggest that extending fiber closer to premises in sparsely populated areas will cost roughly 1.28% of the annual gross domestic product of Sub-Saharan Africa (SSA). Moreover, the total emissions from building FTTnb will account for 0.16%–0.85% of the region’s cross-sector greenhouse gas emissions. Approximately, 550 million of the total Sub-Saharan African population live in areas where FTTnb is likely viable within the next ten years.